Influence of Left Bundle Branch Block on the Electrocardiographic Changes Induced by Acute Coronary Artery Occlusion of Distinct Location and Duration - Jorge, Esther; Solé-González, Eduard; Amorós-Figueras, Gerard; Arzamendi, Dabit; Guerra, Jose M.; Millán, Xavier; Vives-Borrás, Miquel; Cinca, Juan (Frontiers in Physiology, 2019)
Background: Electrocardiographic (ECG) diagnosis of acute myocardial ischemia is hampered in the presence of left bundle branch block (LBBB). Objectives: We analyzed the influence of location and duration of myocardial ischemia on the ECG changes in pigs with LBBB. Methods: LBBB was acutely induced in 14 closed chest anesthetized pigs by local electrical ablation. Thereafter, episodes of 5 min catheter balloon occlusion followed by 10 min reperfusion of the left anterior descending (LAD), left circumflex (LCX), and right (RCA) coronary arteries were done sequentially in 5 pigs. Additionally, a 3-hour occlusion of these arteries was performed separately in the other 9 pigs. A 15-lead ECG including leads V7 to V9 was continuously recorded. Results: Ablation induced LBBB showed QRS widening, loss of r wave in V1, and predominant R waves in V2 to V9. After 5 min of ischemia the occluded artery could be identified in all cases: the LAD by R waves and ST elevation in V1-V3; the LCX by both ST segment elevation in II, III, aVF, V7 to V9 and ST segment depression in V1 to V4; and the RCA by ST depression and new S-waves in all precordial leads. Three hours after coronary occlusion, ST segment changes declined progressively and only the LAD occlusion could be reliably recognized. Conclusion: LBBB did not mask the ECG recognition of the occluded coronary artery during the first 60 min of ischemia, but 3 hours later only the LAD occlusion could be reliably identified. ST elevation in leads V7 to V9 is specific of LCX occlusion and it could be useful in the diagnosis of acute myocardial ischemia in the presence of LBBB.